Anti-radiation fabric and preparation method thereof

By adopting specific raw material combinations and process treatments in radiation-proof fabrics, the problem of insufficient antibacterial and anti-aging performance of existing radiation-proof fabrics is solved, and the efficient anti-radiation, anti-bacterial and anti-aging properties of the fabrics are achieved, which enhances its application potential in a wider range of fields.

CN119843496APending Publication Date: 2025-04-18ZHEJIANG ZHILAN TEXTILE TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510070279.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing radiation-proof fabrics have shortcomings in antibacterial and anti-aging properties, and have poor feel, which limits their application in a wider range of fields.

Method used

A combination of nylon fiber, polyurethane resin, radiation-proof filler, modification finishing agent, anti-aging agent, adhesive, crosslinking agent and thickener in the base cloth layer and radiation-proof coating is prepared through specific processes such as twisting, jacquard machine weaving, alkaline soaking and drying, etc., fabrics with excellent radiation-proof, anti-bacterial and anti-aging properties are prepared.

Benefits of technology

It achieves efficient radiation-proof, antibacterial and anti-aging properties of the fabric, improves the comfort and durability of the fabric, and is suitable for a wider range of application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245513550000061
    Figure BDA0005245513550000061
  • Figure BDA0005245513550000081
    Figure BDA0005245513550000081
  • Figure BDA0005245513550000091
    Figure BDA0005245513550000091
Patent Text Reader

Abstract

The invention discloses an anti-radiation fabric and a preparation method thereof, and belongs to the technical field of anti-radiation fabrics. The anti-radiation fabric comprises a base cloth layer and an anti-radiation coating, the basic layer is prepared from the following raw materials in parts by weight: 30 to 50 parts of polyamide fiber and 10 to 20 parts of polyamide fiber; the anti-radiation coating comprises the following raw materials in parts by weight: 15-20 parts of polyurethane resin, 8-10 parts of anti-radiation filler, 2-3 parts of a modified finishing agent, 4-6 parts of an anti-aging agent, 6-8 parts of an adhesive, 3-5 parts of a cross-linking agent, 4-6 parts of a thickening agent and 100 parts of deionized water. The anti-radiation fabric prepared by the invention has good antibacterial performance and anti-aging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of radiation-proof fabrics, and in particular to a radiation-proof fabric and a preparation method thereof. Background Art

[0002] With the popularization of electronic devices and the development of wireless communication technology, people are exposed to more and more radiation in their daily lives, and the demand for radiation-proof fabrics is also increasing. However, existing radiation-proof fabrics have some obvious shortcomings, such as poor hand feel, poor antibacterial performance, and poor aging resistance. These shortcomings limit the application of radiation-proof fabrics in a wider range of fields. For example, traditional metal fiber blended fabrics, although they have good shielding effects, have a hard hand feel and poor wearing comfort. In addition, some radiation-proof fabrics have deficiencies in antibacterial performance. Although the antibacterial effect can be improved by adding antibacterial agents, these antibacterial agents may gradually become ineffective after multiple washings, resulting in a decrease in the antibacterial performance of the fabric. At the same time, during the use of radiation-proof fabrics, especially in outdoor or high temperature environments, they are easily affected by environmental factors such as ultraviolet rays and ozone, resulting in material aging and decreased radiation protection performance. Therefore, it is particularly important to develop new radiation-proof fabrics that are more comfortable, antibacterial and aging-resistant.

[0003] A Chinese invention patent with publication number CN119121436A discloses a radiation-proof fabric and a preparation method thereof, wherein the radiation-proof fabric is prepared by reacting amino polyacrylonitrile and tetraaldehyde phenylporphyrin to obtain porphyrin-based polyacrylonitrile, reacting porphyrin-based polyacrylonitrile and 3-(2-thienyl)-1-propylamine to obtain thienyl polyacrylonitrile; reacting hydroxyboron nitride and trimethoxy(thien-2-yl)silane to obtain thienyl boron nitride; electrostatically spinning thienyl polyacrylonitrile and thienyl boron nitride to obtain functionalized polyacrylonitrile fibers; weaving the functionalized polyacrylonitrile fibers to obtain functionalized polyacrylonitrile fabrics, and then finishing the functionalized polyacrylonitrile fabrics with 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and thiophene to obtain the radiation-proof fabrics. The radiation-proof fabrics prepared by the invention have good radiation-proof properties, but poor antibacterial and anti-aging properties. Summary of the invention

[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a radiation-proof fabric and a preparation method thereof.

[0005] To achieve the above object, the present invention is implemented through the following technical solutions:

[0006] A radiation-proof fabric comprises a base fabric layer and a radiation-proof coating;

[0007] The basic layer comprises the following raw materials in parts by weight: 30-50 parts of nylon fiber and 10-20 parts of nylon fiber;

[0008] The radiation-proof coating comprises the following raw materials in parts by weight: 15-20 parts of polyurethane resin, 8-10 parts of radiation-proof filler, 2-3 parts of modified finishing agent, 4-6 parts of antioxidant, 6-8 parts of adhesive, 3-5 parts of cross-linking agent, 4-6 parts of thickener, and 100 parts of deionized water;

[0009] The modified finishing agent is prepared by the following method:

[0010] S1: DMSO, thiazo[5,4-d]isothiazol-5-amine, and 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine were added to the reactor, stirred, and heated to 150-170° C., and then a catalyst Cu-Co was added, and the reaction was carried out at 10 atmospheres for 8-10 hours, and the intermediate 1 was obtained after post-treatment;

[0011] S2: Deionized water, emulsifier hexadecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether are added to the reactor, intermediate 1, methyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate and butyl acrylate are mixed evenly, and added dropwise to the reactor, and ultrasonically homogenized for 15-20 minutes to form a pre-emulsion, and then heated to 70-90°C under nitrogen protection, initiator AIBN is added to the reactor, and the reaction is carried out for 6-8 hours, and the modified finishing agent is obtained by post-treatment;

[0012] In step S1, the mass ratio of DMSO, thiazolo[5,4-d]isothiazol-5-amine, and 1-O-1'-(Z)-octadecenyl-2-hydroxy-sn-glycero-3-phosphocholine is 30:(6-8):(8-12);

[0013] In step S2, the mass ratio of the intermediate 1, methyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate, and butyl acrylate is 1:(1-1.2):(1-1.2):(1-1.5).

[0014] The radiation protection filler is one of bismuth oxide, copper oxide and samarium oxide.

[0015] The antioxidant is prepared by the following method:

[0016] S1: Under nitrogen protection, DMSO, 3-chloro-2-hydroxypropyl methacrylate, and potassium hydroxide were added to the reactor in sequence, stirred, and heated to 50-60°C, and then 2,4-dihydroxybenzophenone was added, reacted for 8-10 hours, and post-treated to obtain intermediate 2;

[0017] S2: Add DMSO, intermediate 2, and 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine to the reactor, stir, heat to 120-150°C, then add Cu-Co / Al2O3, react for 8-10h, and post-treat to obtain an antioxidant;

[0018] In step S1, the mass ratio of DMSO, 3-chloro-2-hydroxypropyl methacrylate, and 2,4-dihydroxybenzophenone is 30:(10-15):(5-7);

[0019] In step S2, the mass ratio of DMSO, intermediate 2, and 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine is 30:(5-7):(8-10).

[0020] The adhesive is Loctite 3544F polyurethane adhesive.

[0021] The cross-linking agent is one of hydroxypropyl methacrylate, divinylbenzene and N-hydroxymethyl acrylamide.

[0022] The thickener is a polyurethane thickener.

[0023] A method for preparing a radiation-proof fabric comprises the following steps:

[0024] (1) Weighing 30-50 parts of nylon fiber and 10-20 parts of polyester fiber by weight, twisting the nylon fiber and polyester fiber to obtain a composite yarn, and passing the composite yarn through a jacquard machine to interlace the warp and weft to obtain a plain fabric;

[0025] (2) soaking the plain fabric in an alkaline solution at 75° C. for 30 minutes; taking out the fabric, washing the fabric with deionized water until it becomes neutral, and then drying it in an oven to obtain a base fabric layer;

[0026] (3) Weighing by weight: 15-20 parts of polyurethane resin, 8-10 parts of radiation-proof filler, 2-3 parts of modified finishing agent, 4-6 parts of antioxidant, 6-8 parts of adhesive, 3-5 parts of cross-linking agent, 4-6 parts of thickener, and 100 parts of deionized water; stirring and mixing to obtain a radiation-proof coating;

[0027] (4) The radiation-proof coating is applied to one side of the base fabric layer by a scraper of a coating machine, and then dried in an oven to obtain the radiation-proof fabric.

[0028] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:

[0029] (1) The present invention firstly reacts the hydroxyl group in 1-O-1'-(Z)-octadecenyl-2-hydroxy-sn-glycero-3-phosphocholine with the amino group of thiazo[5,4-d]isothiazol-5-amine to obtain an intermediate 1 having both a quaternary ammonium salt group and a thiazole group, and then polymerizes the intermediate 1 with methyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate, and butyl acrylate to prepare a modified finishing agent with a high-efficiency antibacterial effect.

[0030] (2) The present invention prepares an intermediate 2 by a substitution reaction between the phenolic hydroxyl group at the para-position of the keto group in 2,4-dihydroxybenzophenone and the chlorine in 3-chloro-2-hydroxypropyl methacrylate, and then the hydroxyl group on the intermediate 2 reacts with the amino group of 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine to prepare an antioxidant with excellent anti-aging properties.

[0031] (3) The modified finishing agent prepared by the present invention contains positively charged quaternary ammonium salt groups, which can adsorb negatively charged bacteria through electrostatic force, hydrogen bond force and hydrophobic binding between protein molecules, increase the ability to bind to bacteria, and thus cause damage and destruction to the cell membrane; long-chain hydrophobic groups can be inserted into the lipid layer of the bacterial cell membrane, change the permeability of the cell membrane, cause disorder in the cell membrane structure, and then destroy the membrane structure; in addition, quaternary ammonium salts can bind to proteins and nucleic acids in cells, denature them or inhibit their activity, interfere with the synthesis of nucleic acids and proteins, and thus affect the growth and reproduction of bacteria. At the same time, the modified finishing agent also contains thiazole groups. Thiazole compounds have unique electron-rich nitrogen, sulfur heteroatoms and five-membered heterocyclic structures. Nitrogen atoms are easily non-covalently bound to key bacterial metabolic enzymes, interfering with normal metabolic processes to achieve antibacterial effects. Sulfur atoms can react with bases in proteins to block DNA replication in cells, thereby weakening the growth and reproduction ability of bacteria.

[0032] (4) The antioxidant prepared by the present invention contains a benzophenone group and a histamine group with anti-aging properties. Since 2,4-dihydroxybenzophenone has a small molecular weight and is not resistant to migration, by reacting it with 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine, the molecular weight is increased and the migration resistance is improved. Therefore, adding it to the radiation-proof fabric improves the anti-aging performance of the fabric. DETAILED DESCRIPTION

[0033] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.

[0034] Example 1 Preparation of modified finishing agent:

[0035] S1: 300 g DMSO, 60 g thiazolo[5,4-d]isothiazol-5-amine, and 80 g 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine were added to the reactor, stirred, and heated to 150° C., and then 5 g of catalyst Cu-Co was added, and the reaction was carried out at 10 atmospheres for 10 h. After the reaction was completed, the organic phase was extracted and separated, and the intermediate 1 was obtained by reduced pressure distillation at 60° C. for 3 h;

[0036] S2: Add 50g of deionized water, 0.8g of hexadecyltrimethylammonium bromide and 1.2g of fatty alcohol polyoxyethylene ether to the reactor, stir at 50°C for 20min, mix 5g of intermediate 1, 5g of methyl methacrylate, 5g of 2-(perfluorobutyl)ethyl methacrylate and 5g of butyl acrylate evenly, add them dropwise to the reactor for 5min, then use a cell crusher to perform ultrasonic homogenization for 15min (amplitude 70%, 650W) to obtain a pre-emulsion, then introduce nitrogen, raise the temperature to 70°C, slowly add 0.1g of initiator AIBN to the reactor, and after emulsion polymerization for 8h, cool the reaction system to room temperature, adjust the pH to 7 with 25wt% ammonia water, filter, and vacuum dry at 80°C for 3h to obtain a modified finishing agent.

[0037] Example 2 Preparation of modified finishing agent:

[0038] S1: 300 g DMSO, 70 g thiazo[5,4-d]isothiazol-5-amine, and 100 g 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine were added to the reactor, stirred, and heated to 160°C. Then 8 g of catalyst Cu-Co was added, and the reaction was carried out at 10 atmospheres for 9 h. After the reaction was completed, the organic phase was separated by extraction, and the intermediate 1 was obtained by reduced pressure distillation at 70°C for 2 h. The structural formula of the intermediate 1 is as follows:

[0039]

[0040] Its nuclear magnetic resonance hydrogen spectrum data are as follows:

[0041] 1H NMR(500MHz,Chloroform-d)δ8.37(s,1H),6.87(d,J=7.0Hz,1H),6.13(dtt, J=8.3,1.5,0.9Hz,1H),5.28–5.00(m,1H),4.31–4.12(m,3H),4.10–3.98(m, 1H),3.95–3.76(m,1H),3.63(t,J=3.1Hz,2H),3.17(s,9H),1.99(tdd,J=7.8 ,6.1,1.5Hz,2H),1.48–1.37(m,2H),1.36–1.17(m,28H),1.00–0.78(m,3H).

[0042] S2: 50 g of deionized water, 1.0 g of hexadecyltrimethylammonium bromide and 1.5 g of fatty alcohol polyoxyethylene ether were added to the reactor, and stirred at 60°C for 15 min. 8 g of intermediate 1, 8.8 g of methyl methacrylate, 8.8 g of 2-(perfluorobutyl)ethyl methacrylate and 9.6 g of butyl acrylate were mixed evenly and added dropwise to the reactor for 10 min. The mixture was then ultrasonically homogenized with a cell crusher for 20 min (amplitude 70%, 650 W) to obtain a pre-emulsion. Nitrogen was then introduced, the temperature was raised to 80°C, and 0.1 g of initiator AIBN was slowly added to the reactor. After the emulsion polymerization reaction for 7 h, the reaction system was cooled to room temperature, adjusted to pH 7 with 25 wt% ammonia water, filtered, and vacuum dried at 90°C for 2 h to obtain a modified finishing agent.

[0043] Example 3 Preparation of modified finishing agent:

[0044] S1: 300 g DMSO, 80 g thiazolo[5,4-d]isothiazol-5-amine, and 120 g 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine were added to the reactor, stirred, and heated to 170°C. Then, 10 g of catalyst Cu-Co was added, and the reaction was carried out at 10 atmospheres for 8 h. After the reaction was completed, the organic phase was separated by extraction, and the intermediate 1 was obtained by distillation at 75°C under reduced pressure for 1 h.

[0045] S2: 50g of deionized water, 1.2g of hexadecyltrimethylammonium bromide and 1.8g of fatty alcohol polyoxyethylene ether were added to the reactor, and the mixture was stirred at 70°C for 10min. 10g of intermediate 1, 12g of methyl methacrylate, 12g of 2-(perfluorobutyl)ethyl methacrylate and 15g of butyl acrylate were evenly mixed and then added dropwise to the reactor for 12min. The mixture was then ultrasonically homogenized with a cell crusher for 25min (amplitude 70%, 650W) to obtain a pre-emulsion. Nitrogen was then introduced, the temperature was raised to 90°C, and 0.1g of initiator AIBN was slowly added to the reactor. After the emulsion polymerization reaction for 6h, the reaction system was cooled to room temperature, the pH value was adjusted to 7 with 25wt% ammonia water, filtered, and vacuum dried at 100°C for 1h to obtain a modified finishing agent.

[0046] Example 4 Preparation of antioxidant:

[0047] S1: Under nitrogen protection, 300 g DMSO, 100 g 3-chloro-2-hydroxypropyl methacrylate, and 30 g potassium hydroxide were added to the reactor in sequence, stirred, and heated to 50° C., and then 50 g 2,4-dihydroxybenzophenone was added, and the reaction was carried out for 10 h. After cooling, 500 g ice water was added to precipitate, filtered, and recrystallized with petroleum ether three times (300 g petroleum ether was used each time) to obtain intermediate 2;

[0048] S2: Add 300g DMSO, 50g intermediate 2 and 80g 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine into the reactor, stir, heat to 120°C, then add 5g Cu-Co / Al2O3, react for 10h, and distill at 75°C under reduced pressure for 1h to obtain an antioxidant.

[0049] Example 5 Preparation of antioxidant:

[0050] S1: Under nitrogen protection, 300g DMSO, 125g 3-chloro-2-hydroxypropyl methacrylate, and 45g potassium hydroxide were added to the reactor in sequence, stirred, and heated to 55°C, and then 60g 2,4-dihydroxybenzophenone was added, and the reaction was carried out for 9h. After cooling, 500g ice water was added to precipitate, filtered, and recrystallized with petroleum ether three times (300g petroleum ether was used each time) to obtain intermediate 2, whose structural formula is as follows:

[0051]

[0052] Its nuclear magnetic resonance hydrogen spectrum data are as follows:

[0053] 1H NMR(500MHz,Chloroform-d)δ11.74(s,1H),7.85–7.65(m,3H),7.57–7.44(m,3H),6.70(dd,J=8.4,2.2Hz,1H),6.45(d, J=2.3Hz,1H),5.89–5.42(m,2H),4.44–4.22(m,2H),4.15–3.89(m,3H),3.67–3.37(m,1H),1.93(dd,J=1.4,0.8Hz,3H).

[0054] S2: Add 300g DMSO, 60g intermediate 2, and 90g 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine to the reactor, stir, heat to 130°C, then add 8g Cu-Co / Al2O3, react for 9h, and distill at 70°C for 2h to obtain an antioxidant, the structural formula of which is as follows:

[0055]

[0056] Its nuclear magnetic resonance hydrogen spectrum data are as follows: 1 H NMR(500MHz,Chloroform-d)δ11.74(s,1H),7.81–7.61(m,3H),7.55–7.38(m,3H),6.75–6.56(m,2H),6.46(d,J=2.3Hz,1H),5.86– 5.45(m,2H),4.29(dd,J=11.9,5.3Hz,1H),4.08(ddd,J=41.1,12.0,5.2Hz,2H),3.87(dd,J=12.0,5.2Hz,1H),3.70(ddd,J=15.9,9. 6,7.0Hz,2H),3.57(ddd,J=15.9,9.6,7.0Hz,2H),3.28(dp,J=9.6,5.2Hz,1H),3.06–2.91(m,1H),2.89(dd,J=9.5,8.0Hz,1H),2.3 4(d,J=0.5Hz,6H), 2.03(dddd,J=12.7,9.6,7.0,4.3Hz,2H), 1.93(dd,J=1.4,0.8Hz,3H), 1.78(dddd,J=12.7,9.6,7.0,4.3Hz,2H).

[0057] Example 6 Preparation of antioxidant:

[0058] S1: Under nitrogen protection, 300 g DMSO, 150 g 3-chloro-2-hydroxypropyl methacrylate, and 60 g potassium hydroxide were added to the reactor in sequence, stirred, and heated to 60°C, and then 70 g 2,4-dihydroxybenzophenone was added, and the reaction was carried out for 8 h. After cooling, 500 g ice water was added to precipitate, filtered, and recrystallized with petroleum ether three times (300 g petroleum ether was used each time) to obtain intermediate 2;

[0059] S2: Add 300g DMSO, 70g intermediate 2 and 100g 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine into the reactor, stir, heat to 120°C, then add 10g Cu-Co / Al2O3, react for 8h, and distill at 60°C under reduced pressure for 3h to obtain an antioxidant.

[0060] Example 7 Preparation of radiation-proof fabric:

[0061] (1) Weighing 300 g of nylon fiber and 100 g of polyester fiber, twisting the nylon fiber and the polyester fiber at a twist degree of 1600 twists / m to obtain a composite yarn, and passing the composite yarn through a jacquard machine (at a speed of 700 r / min, with a two-left and two-right linear structure) to obtain a plain weave fabric by interlacing the warp and weft;

[0062] (2) soaking the plain fabric in an alkali solution composed of 6 g / L Na2CO3 and 15 g / L NaOH at 75°C for 30 min; taking out the fabric, rinsing the fabric with deionized water until it becomes neutral, and then drying it in an oven at 65°C for 2 h to obtain a base fabric layer;

[0063] (3) Weigh by weight: 150 g of polyurethane resin, 80 g of radiation-proof filler (bismuth oxide), 20 g of modifying finishing agent (prepared in Example 1), 40 g of antioxidant (prepared in Example 4), and 100 g of adhesive (Loctite). 3544F polyurethane adhesive) 60g, cross-linking agent (hydroxypropyl methacrylate) 30g, thickener (BASF Rheovis PU1341) 40g, deionized water 1000g; stir and mix evenly to obtain a radiation protection coating;

[0064] (4) The radiation protection coating is applied to one side of the base fabric layer by a scraper of a coating machine. The coating is first applied by a floating knife method, wherein the floating knife amount (the height of the scraper from the base platform) is 0.2 mm, and then dried at a temperature of 100°C for 200 seconds. Then, the coating is applied by a suspended knife method, wherein the lower knife amount (the distance of the scraper below the base plane) is 0.5 mm, the knife distance (the distance from the scraper to the base) is 3.5 mm, and then dried at a temperature of 90°C for 180 seconds to obtain the radiation protection fabric.

[0065] Example 8 Preparation of radiation-proof fabric:

[0066] (1) Weighing 400 g of nylon fiber and 150 g of polyester fiber, twisting the nylon fiber and the polyester fiber at a twist degree of 1600 twists / m to obtain a composite yarn, and passing the composite yarn through a jacquard machine (at a speed of 700 r / min, with a two-left and two-right linear structure) to obtain a plain fabric by interlacing the warp and weft;

[0067] (2) soaking the plain fabric in an alkali solution composed of 6 g / L Na2CO3 and 15 g / L NaOH at 75°C for 30 min; taking out the fabric, rinsing the fabric with deionized water until it becomes neutral, and then drying it in an oven at 65°C for 2 h to obtain a base fabric layer;

[0068] (3) Weigh by weight: 180 g of polyurethane resin, 90 g of radiation-proof filler (copper oxide), 25 g of modifying finishing agent (prepared in Example 2), 50 g of antioxidant (prepared in Example 5), and 100 g of adhesive (Loctite). 3544F polyurethane adhesive) 70g, cross-linking agent (divinylbenzene) 40g, thickener (BASF Rheovis PU1341) 50g, deionized water 1000g; stirring and mixing evenly to obtain a radiation protection coating;

[0069] (4) The radiation protection coating is applied to one side of the base fabric layer by a scraper of a coating machine. The coating is first applied by a floating knife method, wherein the floating knife amount (the height of the scraper from the base platform) is 0.2 mm, and then dried at a temperature of 100°C for 200 seconds. Then, the coating is applied by a suspended knife method, wherein the lower knife amount (the distance of the scraper below the base plane) is 0.5 mm, the knife distance (the distance from the scraper to the base) is 3.5 mm, and then dried at a temperature of 90°C for 180 seconds to obtain the radiation protection fabric.

[0070] Example 9 Preparation of radiation-proof fabric:

[0071] (1) Weighing 500 g of nylon fiber and 200 g of polyester fiber, twisting the nylon fiber and the polyester fiber at a twist degree of 1600 twists / m to obtain a composite yarn, and passing the composite yarn through a jacquard machine (at a speed of 700 r / min, with a two-left-two-right linear structure) to obtain a plain fabric by interlacing the warp and weft;

[0072] (2) soaking the plain fabric in an alkali solution composed of 6 g / L Na2CO3 and 15 g / L NaOH at 75°C for 30 min; taking out the fabric, rinsing the fabric with deionized water until it becomes neutral, and then drying it in an oven at 65°C for 2 h to obtain a base fabric layer;

[0073] (3) Weigh by weight: 200 g of polyurethane resin, 100 g of radiation-proof filler (samarium oxide), 30 g of modifying finishing agent (prepared in Example 3), 60 g of antioxidant (prepared in Example 6), and 100 g of adhesive (Loctite). 3544F polyurethane adhesive) 80g, cross-linking agent (N-hydroxymethyl acrylamide) 50g, thickener (BASF Rheovis PU1341) 60g, deionized water 1000g; stirring and mixing evenly to obtain a radiation protection coating;

[0074] (4) The radiation protection coating is applied to one side of the base fabric layer by a scraper of a coating machine. The coating is first applied by a floating knife method, wherein the floating knife amount (the height of the scraper from the base platform) is 0.2 mm, and then dried at a temperature of 100°C for 200 seconds. Then, the coating is applied by a suspended knife method, wherein the lower knife amount (the distance of the scraper below the base plane) is 0.5 mm, the knife distance (the distance from the scraper to the base) is 3.5 mm, and then dried at a temperature of 90°C for 180 seconds to obtain the radiation protection fabric.

[0075] Comparative Example 1

[0076] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that no modifying finishing agent is added in step (3).

[0077] Comparative Example 2

[0078] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, the difference being that the modifying finishing agent in step (3) is replaced by an equal weight of Zinc Antibacterial external finishing agent for fabrics.

[0079] Comparative Example 3

[0080] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that the modifying finishing agent in step (3) is replaced by an equal weight of a modifying finishing agent prepared by the following method:

[0081] S1: 300 g DMSO, 70 g isothiazolo[4,5-B]pyrazine-3-amine, and 100 g 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine were added to the reactor, stirred, and heated to 160°C. Then 8 g of catalyst Cu-Co was added, and the reaction was carried out at 10 atmospheres for 9 h. After the reaction was completed, the organic phase was separated by extraction, and distilled at 70°C under reduced pressure for 2 h to obtain intermediate 3;

[0082] S2: 50 g of deionized water, 1.0 g of hexadecyltrimethylammonium bromide and 1.5 g of fatty alcohol polyoxyethylene ether were added to the reactor, and the mixture was stirred at 60°C for 15 min. 8 g of intermediate 3, 8.8 g of methyl methacrylate, 8.8 g of 2-(perfluorobutyl)ethyl methacrylate and 9.6 g of butyl acrylate were evenly mixed and then added dropwise to the reactor for 10 min. The mixture was then ultrasonically homogenized with a cell crusher for 20 min (amplitude 70%, 650 W) to obtain a pre-emulsion. Nitrogen was then introduced, the temperature was raised to 80°C, and 0.1 g of initiator AIBN was slowly added to the reactor. After the emulsion polymerization reaction for 7 h, the reaction system was cooled to room temperature, the pH value was adjusted to 7 with 25 wt% ammonia water, filtered, and vacuum dried at 90°C for 2 h to obtain a modified finishing agent.

[0083] Comparative Example 4

[0084] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that the modifying finishing agent in step (3) is replaced by an equal weight of a modifying finishing agent prepared by the following method:

[0085] 50g of deionized water, 1.0g of hexadecyltrimethylammonium bromide and 1.5g of fatty alcohol polyoxyethylene ether were added to the reactor, stirred at 60°C for 15min, 8g of 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine, 8.8g of methyl methacrylate, 8.8g of 2-(perfluorobutyl)ethyl methacrylate and 9.6g of butyl acrylate were mixed evenly and added dropwise to the reactor for 10min, followed by ultrasonic homogenization with a cell crusher for 20min (amplitude 70%, 650W) to obtain a pre-emulsion, and then nitrogen was introduced, the temperature was raised to 80°C, 0.1g of initiator AIBN was slowly added to the reactor, and after the emulsion polymerization reaction for 7h, the reaction system was cooled to room temperature, adjusted to pH 7 with 25wt% ammonia water, filtered, and vacuum dried at 90°C for 2h to obtain a modified finishing agent.

[0086] Comparative Example 5

[0087] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that the modifying finishing agent in step (3) is replaced by an equal weight of a modifying finishing agent prepared by the following method:

[0088] 50 g of deionized water, 1.0 g of hexadecyltrimethylammonium bromide and 1.5 g of fatty alcohol polyoxyethylene ether were added to the reactor, stirred at 60 ° C for 15 min, 3.5 g of thiazolyl[5,4-d]isothiazol-5-amine, 5.5 g of 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine, 8 g of methyl methacrylate, 8 g of 2-(perfluorobutyl)ethyl methacrylate, 8 g of butyl acrylate were added. After the esters are evenly mixed, they are added dropwise into the reactor for 10 minutes, followed by ultrasonic homogenization with a cell crusher for 20 minutes (amplitude 70%, 650W) to obtain a pre-emulsion, and then nitrogen is introduced, the temperature is raised to 80°C, and 0.1g of initiator AIBN is slowly added to the reactor. After the emulsion polymerization reaction for 7 hours, the reaction system is cooled to room temperature, adjusted to pH 7 with 25wt% ammonia water, filtered, and vacuum dried at 90°C for 2 hours to obtain a modified finishing agent.

[0089] Comparative Example 6

[0090] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that the modifying finishing agent in step (3) is replaced by an equal weight of a modifying finishing agent prepared by the following method:

[0091] S1: 300 g DMSO, 70 g 2-(4-aminophenyl)benzothiazole, and 100 g 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine were added to the reactor, stirred, and heated to 160° C., and then 8 g of catalyst Cu-Co was added, and the reaction was carried out at 10 atmospheres for 9 h. After the reaction was completed, the organic phase was separated by extraction, and the intermediate 3 was obtained by distillation at 70° C. under reduced pressure for 2 h;

[0092] S2: 50 g of deionized water, 1.0 g of hexadecyltrimethylammonium bromide and 1.5 g of fatty alcohol polyoxyethylene ether were added to the reactor, and the mixture was stirred at 60°C for 15 min. 8 g of intermediate 3, 8.8 g of methyl methacrylate, 8.8 g of 2-(perfluorobutyl)ethyl methacrylate and 9.6 g of butyl acrylate were evenly mixed and then added dropwise to the reactor for 10 min. The mixture was then ultrasonically homogenized with a cell crusher for 20 min (amplitude 70%, 650 W) to obtain a pre-emulsion. Nitrogen was then introduced, the temperature was raised to 80°C, and 0.1 g of initiator AIBN was slowly added to the reactor. After the emulsion polymerization reaction for 7 h, the reaction system was cooled to room temperature, the pH value was adjusted to 7 with 25 wt% ammonia water, filtered, and vacuum dried at 90°C for 2 h to obtain a modified finishing agent.

[0093] Comparative Example 7

[0094] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that the antioxidant in step (3) is replaced by 30g of 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine and 30g of 2,4-dihydroxybenzophenone.

[0095] Comparative Example 8

[0096] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that the antioxidant in step (3) is replaced by an antioxidant prepared by the following method with an equal weight:

[0097] Add 300g DMSO, 60g 2,4-dihydroxybenzophenone, 90g 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine into the reactor, stir, heat to 130°C, then add 8g Cu-Co / Al2O3, react for 9h, and distill at 70°C under reduced pressure for 2h to obtain an antioxidant.

[0098] Comparative Example 9

[0099] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that the antioxidant in step (3) is replaced by an equal weight of the intermediate 2 prepared in step S1 of Example 5.

[0100] Comparative Example 10

[0101] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that the antioxidant in step (3) is replaced by an antioxidant prepared by the following method with an equal weight:

[0102] S1: Under nitrogen protection, 300 g DMSO, 125 g 3-chloro-2-hydroxypropyl methacrylate, and 45 g potassium hydroxide were added to the reactor in sequence, stirred, and heated to 55°C, and then 60 g 2,4-dihydroxybenzophenone was added, and the reaction was carried out for 9 h. After cooling, 500 g ice water was added to precipitate, filtered, and recrystallized with petroleum ether three times (300 g petroleum ether was used each time) to obtain intermediate 2;

[0103] S2: Add 300g DMSO, 60g intermediate 2 and 90g 1-(2-chloroethyl)-2,2,6,6-tetramethylpiperidine into the reactor, stir, heat to 130°C, then add 8g Cu-Co / Al2O3, react for 9h, and distill at 70°C under reduced pressure for 2h to obtain intermediate 1 to obtain an antioxidant.

[0104] Comparative Example 11

[0105] A radiation-proof fabric, the raw material composition and process are basically the same as those of Example 8, except that the antioxidant in step (3) is replaced by an anti-ultraviolet agent prepared by the following method with an equal weight:

[0106] A1: 20 mmol of o-aminophenol, 30 mL of deionized water and 4 mL of 36% concentrated hydrochloric acid were added into a reactor, and a mixed solution of 10 mL of sodium sulfite and anhydrous copper sulfate dissolved in deionized water in a ratio of 0.65 g:0.04 g:5 mL was added dropwise under stirring at -5°C and a stirring rate of 250 r / min. After the addition was completed, the reaction was continued with stirring for 1 h. After the reaction was completed, the reaction product was vacuum filtered and the filtrate was collected to obtain an intermediate 1 solution;

[0107] A2: 10 mmol of m-phenylenediamine, 20 mL of deionized water and 1 mL of 36% concentrated hydrochloric acid were added to the reactor, and 20 mL of the intermediate 1 solution was added dropwise while stirring at -5°C and a stirring rate of 250 r / min. After the addition was completed, the reaction was continued for 5 minutes while stirring, and then 10 mL of 40% sodium acetate solution was added dropwise while stirring. After the addition was completed, the temperature was raised to 20°C and the reaction was continued for 2 hours. After the reaction was completed, the pH of the reaction product was adjusted to 8 with 22% concentrated ammonia water, and then vacuum filtered. The filter cake was washed twice with distilled water and then placed in a vacuum drying oven to dry to constant weight to obtain intermediate 2;

[0108] A3: 10 mmol of intermediate 2, 50 mL of methanol solution, 6.0 g of anhydrous copper sulfate, 10 mL of deionized water and 25 mL of 22% concentrated ammonia water were added to the reactor, and the mixture was heated to reflux reaction while stirring at a stirring rate of 250 r / min. The heating rate was controlled to 2°C / min, and the mixture was stirred at a constant temperature for 2 h. After the reaction, the reaction product was cooled to room temperature, vacuum filtered, and the filter cake was washed twice with distilled water, and then dissolved in 20 mL of 5 mol / L hydrochloric acid solution, stirred for 1 h, and then 12 mL of 10% ammonia solution was added and stirred for 10 min. The mixture was vacuum filtered, and the filter cake was washed twice with distilled water, and then placed in a vacuum drying oven to dry to constant weight to obtain intermediate 3;

[0109] A4: 10 mL of dichloromethane and 15 mmol of chloroacetyl chloride were added to the reactor, and 10 mL of 2,4-dihydroxybenzophenone and triethylamine were dissolved in dichloromethane at a ratio of 0.1 mol: 0.15 mol: 50 mL, and the mixture was added dropwise while stirring at -5 °C and a stirring rate of 350 r / min. After the addition was completed, the mixture was heated to 20 °C and stirred for 6 h. After the reaction was completed, the reaction product was washed with distilled water twice, allowed to stand for separation, anhydrous methanol was added to the organic phase, evaporated and concentrated to precipitate, the precipitate was dissolved in dichloromethane, and petroleum ether was added to precipitate, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried to constant weight to obtain intermediate 4;

[0110] A5: Add 60mmol of intermediate 3, 60mmol of triethylamine, 50mL of dichloromethane and 60mmol of intermediate 4 into a reactor, stir and react for 6h at -5℃ and a stirring rate of 300r / min. After the reaction, wash the reaction product with distilled water twice, let it stand and separate the liquids, evaporate and concentrate the organic phase to half its volume, add 10mL of anhydrous methanol thereto, and then continue to evaporate and concentrate, let it stand and cool to precipitate, vacuum filter, dissolve the filter cake in dichloromethane, then add petroleum ether to precipitate, vacuum filter, place the filter cake in a vacuum drying oven and dry it to constant weight to obtain an anti-ultraviolet agent.

[0111] Comparative Example 12

[0112] A radiation-proof fabric is prepared using the raw material composition, proportion and method of Example 2 of the Chinese invention patent with publication number CN119121436A.

[0113] The polyurethane resin model used in the embodiments and comparative examples of the present application is PU-330A, purchased from Hefei Huayue New Material Technology Co., Ltd.; the nylon fibers used are 185 roots / 10cm×124 roots / 10cm, with a gram weight of 182g / m; the polyester fibers are 202 roots / 10cm×154 roots / 10cm, with a gram weight of 205g / m, purchased from Zhejiang Fa Textile Printing and Dyeing Co., Ltd.; the fatty alcohol polyoxyethylene ether used is AEO-9 type.

[0114] The Cu-Co catalyst used in this application was prepared by the following method:

[0115] Dissolve 7.5gCu(NO3)2 and 5gCo(NO3)2·6H2O in 20ml deionized water, stir at room temperature for 12h, then rotary evaporate at 40℃ for 2h, vacuum dry at 110℃ for 8h, then grind the obtained powder and calcine at 400℃ for 4h to obtain the catalyst Cu-Co.

[0116] The Cu-Co / Al2O3 catalyst used in this application is prepared by the following method:

[0117] Dissolve 7.5gAl2O3, 7.5gCu(NO3)2 and 5gCo(NO3)2·6H2O in 30ml deionized water, stir at room temperature for 12h, then rotary evaporate at 40℃ for 2h, vacuum dry at 110℃ for 8h, then grind the obtained powder and calcine at 400℃ for 4h to obtain the catalyst Cu-Co / Al2O3.

[0118] The radiation protection fabrics prepared in Examples 7-9 and Comparative Examples 1-12 of the present application were subjected to an antibacterial rate test. The test method was carried out in accordance with GB / T20944.3-2008 "Evaluation of Antibacterial Properties of Textiles Part 3: Oscillation Method". The washing method was carried out using a washing color fastness tester. The antibacterial rate of the fabric was tested after 30 washes. The test results are shown in Table 1.

[0119] The radiation-proof fabrics prepared in Examples 7-9 and Comparative Examples 1-12 of the present application were subjected to a breaking strength test before and after aging. The test method was carried out in accordance with GB / T 3923.1-2013. The samples were cut into 30 cm × 5 cm fabrics along the warp and weft directions, respectively. The AP-808 tensile testing machine (Ai Pei Technology Co., Ltd.) was used for the test at a constant tensile rate of 200 mm / min. Five samples were tested in each direction.

[0120] Fabric aging method: The fabric was continuously exposed to 1000W high pressure mercury lamp UV aging box for 800 hours. The test results are shown in Table 1.

[0121] Table 1

[0122]

[0123] It can be seen from Table 1 that the antibacterial rate of the radiation-proof fabric prepared by the present invention is higher than 99%, the warp strength after aging is about 600N, and the weft strength is about 300N, which has excellent antibacterial and anti-aging properties.

[0124] The raw material composition and process of Comparative Example 1 are basically the same as those of Example 8, except that no modifying finishing agent is added in step (3). It can be seen from the data in Table 1 that the antibacterial rates against Candida albicans and Staphylococcus aureus are both around 40%, the warp strength after aging is 598N, and the weft strength is 296N. The aging performance is good, but the antibacterial performance is poor, indicating that the antibacterial effect of the fabric prepared without adding the modifying finishing agent is poor.

[0125] The raw material composition and process of Comparative Example 2 are basically the same as those of Example 8, except that the modifying finishing agent is replaced by an equal weight of Zinc As can be seen from the data in Table 1, the antibacterial rates of the antibacterial agents for fabrics against Candida albicans and Staphylococcus aureus are both around 82%, the warp strength after aging is 601N, and the weft strength is 298N, indicating that the antibacterial performance of the commercially available antibacterial finishing agents is average.

[0126] The raw material composition and process of Comparative Example 3 are basically the same as those of Example 8, except that the thiazolo[5,4-d]isothiazol-5-amine in step S1 during the preparation of the modified finishing agent is replaced by isothiazolo[4,5-B]pyrazine-3-amine. It can be seen from the data in Table 1 that the antibacterial rates against Candida albicans and Staphylococcus aureus are 96.52% and 97.45%, respectively, and the antibacterial effect is poor.

[0127] The raw material composition and process of Comparative Example 4 are basically the same as those of Example 8, except that when preparing the modified finishing agent, the intermediate 2 in step S2 is replaced by an equal weight of 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine. It can be seen from the data in Table 1 that the antibacterial rates against Candida albicans and Staphylococcus aureus are both around 93%, and the antibacterial effect is poor.

[0128] The raw material composition and process of Comparative Example 5 are basically the same as those of Example 8, except that the modified finishing agent is replaced by a copolymer of thiazolyl[5,4-d]isothiazol-5-amine and 1-O-1'-(Z)-octadecenyl-2-hydroxy-sn-glycero-3-phosphocholine with methyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate, and butyl acrylate. It can be seen from Table 1 that the antibacterial rates of Candida albicans and Staphylococcus aureus are both around 97%. When the quaternary ammonium salt compound and the thiazole compound do not react and are added alone, the antibacterial effect is not as good as that of the radiation-proof fabric prepared after the two react.

[0129] The raw material composition and process of Comparative Example 6 are basically the same as those of Example 8, except that the thiazolyl[5,4-d]isothiazole-5-amine in step S1 during the preparation of the modified finishing agent is replaced with 2-(4-aminophenyl)benzothiazole. It can be seen from the data in Table 1 that the antibacterial rates against Candida albicans and Staphylococcus aureus are both around 98%, and the antibacterial effect is not as ideal as that of the present application.

[0130] The raw material composition and process of Comparative Example 7 are basically the same as those of Example 8, except that the antioxidant is replaced by equal weights of 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine and 2,4-dihydroxybenzophenone. It can be seen from the data in Table 1 that the anti-aging effect is poor.

[0131] The raw material composition and process of Comparative Example 8 are basically the same as those of Example 8, except that the antioxidant is replaced by an antioxidant synthesized by the reaction of 2,4-dihydroxybenzophenone and 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine. It can be seen from the data in Table 1 that the anti-aging effect is poor.

[0132] The raw material composition and process of Comparative Example 9 are basically the same as those of Example 8, except that the antioxidant is replaced by the intermediate 2 prepared in step S1 of Example 5. It can be seen from the data in Table 1 that the anti-aging performance is poor.

[0133] The raw material composition and process of Comparative Example 10 are basically the same as those of Example 8, except that 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine in step S2 in the preparation of the antioxidant is replaced by 1-(2-chloroethyl)-2,2,6,6-tetramethylpiperidine. It can be seen from the data in Table 1 that the anti-aging performance is poor.

[0134] The raw material composition and process of Comparative Example 11 are basically the same as those of Example 8, except that the preparation method of the antioxidant is different. It can be seen from the data in Table 1 that the anti-aging performance is poor.

[0135] Comparative Example 12 is a radiation-proof fabric prepared using the raw material composition, ratio and method of Example 2 of the Chinese invention patent with publication number CN119121436A. It can be seen from the data in Table 1 that the anti-aging performance and antibacterial performance are not as good as the radiation-proof fabric prepared in this application.

[0136] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A radiation-proof fabric, characterized in that: Including base fabric layer and radiation protection coating; The basic layer comprises the following raw materials in parts by weight: 30-50 parts of nylon fiber and 10-20 parts of nylon fiber; The radiation-proof coating comprises the following raw materials in parts by weight: 15-20 parts of polyurethane resin, 8-10 parts of radiation-proof filler, 2-3 parts of modified finishing agent, 4-6 parts of antioxidant, 6-8 parts of adhesive, 3-5 parts of cross-linking agent, 4-6 parts of thickener, and 100 parts of deionized water; The modified finishing agent is prepared by the following method: S1: DMSO, thiazo[5,4-d]isothiazol-5-amine, and 1-O-1'-(Z)-octadecene-2-hydroxy-sn-glycero-3-phosphocholine were added to the reactor, stirred, and heated to 150-170° C., and then a catalyst Cu-Co was added, and the reaction was carried out at 10 atmospheres for 8-10 hours, and the intermediate 1 was obtained after post-treatment; S2: Deionized water, emulsifier hexadecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether are added into the reactor, intermediate 1, methyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate and butyl acrylate are mixed evenly, and added dropwise into the reactor, and ultrasonically homogenized for 15-20 minutes to form a pre-emulsion, and then heated to 70-90°C under nitrogen protection, initiator AIBN is added into the reactor, and the reaction is carried out for 6-8 hours, and the modified finishing agent is obtained by post-treatment.

2. The radiation protection fabric according to claim 1, characterized in that: In step S1, the mass ratio of DMSO, thiazolo[5,4-d]isothiazol-5-amine, and 1-O-1'-(Z)-octadecenyl-2-hydroxy-sn-glycero-3-phosphocholine is 30:(6-8):(8-12).

3. The radiation protection fabric according to claim 1, characterized in that: In step S2, the mass ratio of the intermediate 1, methyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate, and butyl acrylate is 1:(1-1.2):(1-1.2):(1-1.5).

4. The radiation protection fabric according to claim 1, characterized in that: The radiation protection filler is one of bismuth oxide, copper oxide and samarium oxide.

5. The radiation protection fabric according to claim 1, characterized in that: The antioxidant is prepared by the following method: S1: Under nitrogen protection, DMSO, 3-chloro-2-hydroxypropyl methacrylate, and potassium hydroxide were added to the reactor in sequence, stirred, and heated to 50-60°C, and then 2,4-dihydroxybenzophenone was added, reacted for 8-10 hours, and post-treated to obtain intermediate 2; S2: Add DMSO, intermediate 2, and 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine to the reactor, stir, heat to 120-150°C, then add Cu-Co / Al2O3, react for 8-10h, and post-treat to obtain an antioxidant; In step S1, the mass ratio of DMSO, 3-chloro-2-hydroxypropyl methacrylate, and 2,4-dihydroxybenzophenone is 30:(10-15):(5-7); In step S2, the mass ratio of DMSO, intermediate 2, and 1-(4,6-dimethyl-2-pyrimidinyl)-4-piperidinamine is 30:(5-7):(8-10).

6. The radiation protection fabric according to claim 1, characterized in that: The adhesive is Loctite HHD 3544F polyurethane adhesive.

7. The radiation protection fabric according to claim 1, characterized in that: The cross-linking agent is one of hydroxypropyl methacrylate, divinylbenzene and N-hydroxymethyl acrylamide.

8. The radiation protection fabric according to claim 1, characterized in that: The thickener is a polyurethane thickener.

9. A method for preparing the radiation-proof fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weighing 30-50 parts of nylon fiber and 10-20 parts of polyester fiber by weight, twisting the nylon fiber and polyester fiber to obtain a composite yarn, and passing the composite yarn through a jacquard machine to interlace the warp and weft to obtain a plain fabric; (2) soaking the plain fabric in an alkaline solution at 75° C. for 30 minutes; taking out the fabric, washing the fabric with deionized water until it becomes neutral, and then drying it in an oven to obtain a base fabric layer; (3) Weighing by weight: 15-20 parts of polyurethane resin, 8-10 parts of radiation-proof filler, 2-3 parts of modified finishing agent, 4-6 parts of antioxidant, 6-8 parts of adhesive, 3-5 parts of cross-linking agent, 4-6 parts of thickener, and 100 parts of deionized water; stirring and mixing to obtain a radiation-proof coating; (4) The radiation-proof coating is applied to one side of the base fabric layer by a scraper of a coating machine, and then dried in an oven to obtain the radiation-proof fabric.

Citation Information

Patent Citations

  • Anti-radiation fabric and preparation method thereof

    CN119121436A